SPIRITUAL FACTORS OF SOCIAL RELATIONS OF SOCIETY - Aliqulov , Begzod (Journal of Contemporary World Studies, 2024)
This article provides information on the spiritual factors present in society and social relations. Further details are given on the concept of society, definitions of society and types of society, the process of formation of society.